Taxonomic revision of the South American subgenus Augochloropsis (Glyptobasia) (Hymenoptera: Apidae: Halictinae) - Celis, Cindy Julieth; Melo, Gabriel A. R. (Zootaxa, 2024)
Augochloropsis (Glyptobasia) Moure, a small Neotropical subgenus, is revised, with the description of a new species, Augochloropsis aenea sp. nov., from Puno, southern Peru. Augochloropsis (Glyptobasia) comprised the two nominal species, A. bertonii (Schrottky) with a bluish-violet body coloration and A. chloera (Moure) with a bright green body coloration, both species have coarse integumental punctures and an unusual propodeal structure. We interpret these striking color differences, as a case of color polymorphism within a single species. Therefore, Moure’s taxon is placed as a junior synonym of A. bertonii. An identification key for the species and a distribution map are also provided.